M/E/A/N/I/N/G : an anthology of artists' writings, theory, and criticism - Bee, Susan; Schor, Mira (Duke backfile, 2000)
A collection of writings from the influential feminist art journal M/E/A/N/I/N/G, with a forward by Johanna Drucker.